Anchoring of Ag6Si2O7 nanoparticles on α-Fe2O3 short nanotubes as a Z-scheme photocatalyst for improving their photocatalytic performances. Issue 32 (27th July 2016) - Liu, Jun; Wu, Wei; Tian, Qingyong; Dai, Zhigao; Wu, Zhaohui; Xiao, Xiangheng; Jiang, Changzhong
Abstract : α-Fe2 O3 /Ag6 Si2 O7 p–n heterostructures with well-defined morphology were synthesized and their photocurrent intensity is improved 62 times compared with pure α-Fe2 O3 SNTs. Abstract : Coupling two different semiconductors to form composite photocatalysts is the most significant method for environmental remediation. In this regard, tube-like α-Fe2 O3 /Ag6 Si2 O7 heterostructures are synthesized via anchoring p-type Ag6 Si2 O7 nanoparticles (NPs) on the surface of n-type α-Fe2 O3 short nanotubes (SNTs) by conventional wet-chemical routes. α-Fe2 O3 SNTs are firstly fabricated by a hydrothermal method with the assistance of dihydrogen phosphate and sulphate. Then, Ag6 Si2 O7 NPs are anchored on α-Fe2 O3 SNTs by an in situ deposition method, and the α-Fe2 O3 /Ag6 Si2 O7 p–n heterostructures are finally obtained. The morphologies, crystal structure, photocatalytic performance and photocurrent properties of as-synthesized α-Fe2 O3 /Ag6 Si2 O7 heterostructures are investigated. Six organic dyes are used for determining the high-efficiency Z-scheme photocatalytic activities of the as-obtained photocatalysts under ultraviolet and visible light (mercury lamp, 300 W). Compared with pure α-Fe2 O3 SNTs, the photocurrent intensity of the α-Fe2 O3 /Ag6 Si2 O7 heterostructures is improved 62 times. The enhanced significant photocatalytic performance of α-Fe2 O3 /Ag6 Si2 O7 heterostructures could be attributed to charge transfer between Ag6 Si2 O7 NPs and the charge separation between Ag6 Si2 O7 NPs and α-Fe2 O3 SNTs. These composite heterostructures are proposed to be an example for the preparation of other composite silicate photocatalysts for practical application in environmental remediation issues.